Efficacy of Lactulose and Polyethylene Glycol in the Treatment of Hepatic Encephalopathy - Pathak, Rahul; Lamsal, Manoj; Bhusal, Mohan (Journal of Nepal Health Research Council, 2025)
Background: Hepatic encephalopathy presents a significant clinical challenge in individuals with advanced liver dysfunction, manifesting as confusion, altered consciousness, and personality changes. This study aimed to compare the efficacy of lactulose and polyethylene glycol in managing Hepatic encephalopathy.Methods: The study is conducted at Tribhuvan University Teaching Hospital in Nepal; the study enrolled 45 cirrhotic patients with altered mental status in each study group. Ethical approval and informed consent were obtained. The basic demographic and clinical data were collected, including laboratory investigation and precipitating factors for Hepatic encephalopathy. The severity of Hepatic encephalopathy was assessed using the West Haven Criteria.Results: In this study there was significant difference between two groups in terms of mean time taken for complete resolution of hepatic encephalopathy, with mean of 2.98 ± 2.129 days in Polyethylene Glycol group compared to mean of 4.67 ± 3.076 days in Lactulose group, with a significant p-value of 0.004. There was also significant difference in length of hospital stay between two groups, with a mean hospital stay of 6.36 ± 3.654 days in Polyethylene Glycol group compared to 9.70 ±5.388 days in Lactulose group, with a significant p-value of 0.001.Conclusions: In conclusion, polyethylene glycol showed promising results in the treatment of Hepatic encephalopathy compared to lactulose polyethylene glycol. demonstrated an improvement and quicker resolution of Hepatic encephalopathy symptoms, highlighting its potential as a cost effective and safe alternative for managing Hepatic encephalopathy in cirrhotic patients.Keywoards: Hepatic encephalopathy; lactulose; polyethylene glycol.